2021
DOI: 10.1038/s41598-021-02073-w
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of crocin loaded in nanoniosomes and their effects on ischemia–reperfusion injuries in rat kidney

Abstract: As a powerful antioxidant compound, crocin can partially protect against renal ischemia/reperfusion (I/R) injuries. The encapsulation of components in niosomes (non-ionic surfactant-based vesicle) as nano-sized carrier systems has been proposed as they improve the solubility, stability, and bioavailability of drugs. Herein, the encapsulation of crocin in nano-niosomes and the effects of crocin-loaded nano-niosomes on renal ischemia/reperfusion-induced damages were evaluated. Nano-niosomes containing crocin wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Additionally, the small size of NPs enables more effective interaction with tumor cells. Previous studies have reported the anticancer properties of crocin, as well as the effects of Nanosystems carrying crocin 21 , 44 . However, no research has been conducted on cellulose nanocarriers modified with CTAB as a cationic surfactant and FA to deliver crocin to cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the small size of NPs enables more effective interaction with tumor cells. Previous studies have reported the anticancer properties of crocin, as well as the effects of Nanosystems carrying crocin 21 , 44 . However, no research has been conducted on cellulose nanocarriers modified with CTAB as a cationic surfactant and FA to deliver crocin to cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the protective effect of Saffron on oxidative stress in different tissues such as abdominal organs, kidney, testis, and endothelial cells [ 21 , 41 46 ]. Crocin, safranal, carotene and crocetin as the most abundant constituents of Saffron stigmas, represent antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Crocin, safranal, carotene and crocetin as the most abundant constituents of Saffron stigmas, represent antioxidant effects. Noticeably, Saffron extract is mentioned as a potent anti-oxidant with high ability to scavenge ROS, especially superoxide anions and hydrogen peroxide (H 2 O 2 ) resulting in inhibitory effect on lipid peroxidation [ 22 , 29 , 32 , 41 ]. Also, Saffron is suggested in autoimmune encephalomyelitis, and cerebral ischemia [ 23 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In-vitro drug release: The in-vitro drug release study is carried out in two medium: Phosphate buffer and gastrointestinal pH medium 59,60 .…”
Section: Semmentioning
confidence: 99%